Impact of Saline Water Irrigation on Soil Salinity, Growth, and Productivity of Triticale in Sandy Soil - Abd El Baki, Hassan M.; Fujimaki, Haruyuki; Toderich, Kristina; Nana, Jean Bosco; Qureshi, Asad S. (Soil systems, 2025)
Salinity and water scarcity are among the major environmental challenges requiring the use of non-conventional water sources and the adoption of salt-tolerant crops. We assessed the impact of irrigation with different concentrations of NaCl: 50 mM and 150 mM on the growth parameters and yield of triticale, soil salinity, distribution of active root density, and concentrations of Na+ and NO3− ions at harvest compared to freshwater under zero leaching conditions. Irrigation was applied on a daily basis based on weight measurements of micro-lysimeter pots. Growth parameters, including plant height, LAI, number of leaves, number of tillers, and soil salinity, were observed across the growing season. Spatial distributions of soil salinity, normalized root length density (NRLD), concentrations of Na+ and NO3− in soil profile were measured in two dimensions. The results indicate that irrigating with 150 mM of NaCl H2O significantly affected the crop growth, causing salts, particularly Na+, to reside in the topsoil, reducing NRLD with soil depth, crop water demand, and NO3− uptake. The application of 150 mM and 50 mM of NaCl H2O reduced crop water use by 4 and 2.6 times as well as grain yield by 97% and 42%, respectively, compared to freshwater. This shows that irrigation with concentration equal to or higher than 150 mM NaCl will result in very low production. To achieve higher yield and crop water productivity, irrigation with NaCl concentration of 50 mM or less is recommended to grow triticale in marginal regions with limited freshwater resources.